Kesiapan Lulusan Sekolah Kejuruan sebagai Tenaga Kerja yang Berkarakter Profesional dan Mandiri - Ittihad Ittihad (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
Developing a profesional culture in schools is done by: (1) implementing a strict new student admission system, (2) school orientation activities on new students, (3) imposing school rules and compensation tasks, (4) implementing a solid learning system, and (5) implementing graduate marketing. Positive habits that form the basis of profesional culture can grow and develop in Shaykh Zainuddin NW Anjani Vocational School starting with the process of internalizing the noble values ​​of profesional culture in students and teachers alike. In students the internalization process occurs because of things as follows: (1) instilling awareness about profesional cultural values ​​by teachers and school leaders, (2) students' internal factors (encouragement from themselves), and (3) adjusting themselves to an environment that has been cultured profesionally. In the teacher the process occurs because: (1) the adaptation of the teacher to the tasks of the environment, (2) the employment status has, and (3) their assumption that carrying out the duties as a teacher is